First record of Hamacantha (Porifera, Demospongiae, Merliida, Hamacanthidae) from Japan, with description of two new species - Ise, Yuji; Woo, Sau Pinn; Tan, Shau Hwai; Fujita, Toshihiko (Zootaxa, 2019)
Two new species of thinly encrusting sponge Hamacantha (Demospongiae, Merliida, Hamacanthidae) are described from Japan. Hamacantha (Vomerula) mamoi sp. nov. was collected from Sagami Bay, and Hamacantha (Vomerula) umisachii sp. nov. from off Hachijo Island. This is the first record of Hamacantha and the Hamacanthidae from Japan. H. (V.) mamoi sp. nov. is characterized by having styles, two types of diancistras and one of sigmas. Only two known species have the same spicule composition: H. (V.) acerata Lévi, 1993 and H. (V.) esperioides Ridley & Dendy, 1886, described from New Caledonia, and south-west Africa and south-east South America, respectively. H. (V.) acerata has larger diancistras and much smaller sigmas compared with those of H. (V.) mamoi sp. nov. H. (V.) esperioides can be separated by having larger styles and smaller sigmas than those of H. (V.) mamoi sp. nov. H. (V.) umisachii sp. nov is characterized by having styles, diancistras, cyrtancistra-like diancistras and sigmas. Hamacantha (V.) carteri Topsent, 1904 seems to have similar spicule composition, however the size of all spicule types is different.